2005
DOI: 10.1074/jbc.m508762200
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Polymerization (DP) of Polysialic Acid (PolySia) on Neural Cell Adhesion Molecules (N-CAMs)

Abstract: ␣2,8-Linked polysialic acid (polySia) is a structurally unique antiadhesive glycotope that covalently modifies N-linked glycans on neural cell adhesion molecules (N-CAMs). These sugar chains play a key role in modulating cell-cell interactions, principally during embryonic development, neural plasticity, and tumor metastasis. The degree of polymerization (DP) of polySia chains on N-CAM is postulated to be of critical importance in regulating N-CAM function. There are limitations, however, in the conventional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 61 publications
1
46
0
1
Order By: Relevance
“…Given the relatively homogenous band centered at 150 kDa, but ranging from 130 to 200 kDa, that is detected on an immunoblot of protein in a cell lysate probed with mAb 735, though, we propose that NRP-2 is the predominant carrier of PSA in dendritic cells. The broadness of a band of polysialylated protein on immunoblot does not necessarily indicate the presence of multiple proteins, as PSA chains vary greatly in size and generate heterogeneity in protein molecular mass (42,43). It is of note that although NRP-1 and NRP-2 share extensive amino acid sequence homology, we found that NRP-1 is not polysialylated in dendritic cells (data not shown).…”
Section: Discussionmentioning
confidence: 49%
“…Given the relatively homogenous band centered at 150 kDa, but ranging from 130 to 200 kDa, that is detected on an immunoblot of protein in a cell lysate probed with mAb 735, though, we propose that NRP-2 is the predominant carrier of PSA in dendritic cells. The broadness of a band of polysialylated protein on immunoblot does not necessarily indicate the presence of multiple proteins, as PSA chains vary greatly in size and generate heterogeneity in protein molecular mass (42,43). It is of note that although NRP-1 and NRP-2 share extensive amino acid sequence homology, we found that NRP-1 is not polysialylated in dendritic cells (data not shown).…”
Section: Discussionmentioning
confidence: 49%
“…However, Nakata and Troy (37) reported the presence of small amounts of polySia with DPs of up to ϳ400 in Neuro2A cells stably transfected with ST8SiaIV using endo-␤-galactosidase for enzymatic release of polySia. Further studies are required to investigate whether such long polymers are restricted to cellular systems overexpressing polysialyltransferases or whether more sensitive methods are required for the detection of polySia chains directly from mouse brain.…”
Section: Discussionmentioning
confidence: 99%
“…2 is a polymer of sialic acid with a degree of polymerization (DP) ranging from 8 to 400 (1)(2)(3)(4) and is mainly attached to neural cell adhesion molecule (NCAM) in vertebrates (1). PolySia is expressed in brains during embryonic and postneonatal development and mostly disappears in adult brains, although NCAM expression levels remain unchanged (1,5,6).…”
Section: Polysiamentioning
confidence: 99%